2021
DOI: 10.3389/fmicb.2020.605962
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Combination of Linezolid and Fosfomycin Closing Each Other’s Mutant Selection Window to Prevent Enterococcal Resistance

Abstract: Enterococci, the main pathogens associated with nosocomial infections, are resistant to many common antibacterial drugs including β-lactams, aminoglycosides, etc. Combination therapy is considered an effective way to prevent bacterial resistance. Preliminary studies in our group have shown that linezolid combined with fosfomycin has synergistic or additive antibacterial activity against enterococci, while the ability of the combination to prevent resistance remains unknown. In this study, we determined mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 70 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…According to the in vitro dynamic time-kill curve, the maximum bactericidal rate of coadministration was not significantly increased relative to fosfomycin at 4 to 6 h, but the bactericidal effect became progressively stronger after 6 h. This might occur because linezolid limits the rapid bactericidal effect of fosfomycin during early bacterial reproduction, but in later stages, when bacterial populations reach a stable period, the combination of the two drugs produces a more potent bactericidal effect. Moreover, in a previous study, we found that the combination of linezolid and fosfomycin against Enterococcus could effectively close the resistance mutation-selection windows of the other, which is a potential mechanism to explain the ability of coadministration to inhibit bacterial regeneration at a later stage ( 8 ). Additionally, the production of enterococcal biofilms in an in vitro model protected a subpopulation of bacterial inoculum from fosfomycin, thereby regenerating a subpopulation when fosfomycin concentration was below the MIC of the isolates ( 11 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…According to the in vitro dynamic time-kill curve, the maximum bactericidal rate of coadministration was not significantly increased relative to fosfomycin at 4 to 6 h, but the bactericidal effect became progressively stronger after 6 h. This might occur because linezolid limits the rapid bactericidal effect of fosfomycin during early bacterial reproduction, but in later stages, when bacterial populations reach a stable period, the combination of the two drugs produces a more potent bactericidal effect. Moreover, in a previous study, we found that the combination of linezolid and fosfomycin against Enterococcus could effectively close the resistance mutation-selection windows of the other, which is a potential mechanism to explain the ability of coadministration to inhibit bacterial regeneration at a later stage ( 8 ). Additionally, the production of enterococcal biofilms in an in vitro model protected a subpopulation of bacterial inoculum from fosfomycin, thereby regenerating a subpopulation when fosfomycin concentration was below the MIC of the isolates ( 11 ).…”
Section: Discussionmentioning
confidence: 91%
“…Hence, combination therapy has been proposed to alleviate the development of drug resistance and increase efficacy. Previous studies have confirmed that linezolid combined with fosfomycin (FOF) can effectively inhibit vancomycin-resistant and -sensitive Enterococcus strains ( 7 , 8 ). However, these studies have been limited to the qualitative determination of the synergistic effects of the two drugs without a quantitative perspective on the mechanisms by which the drugs act on bacteria.…”
Section: Introductionmentioning
confidence: 98%
“… 30 However, this value was twofold higher than that in clinical trial. Combination is another solution, Jiang et al 36 observed that linezolid combined with fosfomycin closing each other’s mutant selection window through Mueller–Hinton Agar dilution method.…”
Section: Discussionmentioning
confidence: 99%
“…Qi et al (14) suggested linezolid in combination with fosfomycin as a potential treatment for VRE infection. In a study of the synergistic combination of linezolid and fosfomycin, Jiang et al (15) showed that the combination effectively inhibits the selection of enterococcal-resistant mutants by closing each other's mutant selection window. Given the limited treatment options available, new combination therapies of the two above-mentioned drugs represent a potential treatment for VRE.…”
Section: Introductionmentioning
confidence: 99%